2022
DOI: 10.32604/cmc.2022.018181
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Based Camera Prioritization in Large Scale Surveillance Networks

Abstract: Digital surveillance systems are ubiquitous and continuously generate massive amounts of data, and manual monitoring is required in order to recognise human activities in public areas. Intelligent surveillance systems that can automatically identify normal and abnormal activities are highly desirable, as these would allow for efficient monitoring by selecting only those camera feeds in which abnormal activities are occurring. This paper proposes an energy-efficient camera prioritisation framework that intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…To monitor complex video surveillance, CNNs are often used for tasks such as activity and action recognition, anomaly detection, classification, and object detection [31][32][33][34][35], as well as a wide range of other identification, medical image diagnosis, video summarization, and segmentation applications [36][37][38][39][40]. The CNN architecture comprises three main components: the Convolution Layer (CL), pooling layer, and fully linked layer.…”
Section: E-firenet Frameworkmentioning
confidence: 99%
“…To monitor complex video surveillance, CNNs are often used for tasks such as activity and action recognition, anomaly detection, classification, and object detection [31][32][33][34][35], as well as a wide range of other identification, medical image diagnosis, video summarization, and segmentation applications [36][37][38][39][40]. The CNN architecture comprises three main components: the Convolution Layer (CL), pooling layer, and fully linked layer.…”
Section: E-firenet Frameworkmentioning
confidence: 99%
“…(7) Establishing a blockchain for video surveillance equipment: In a technological environment where digital surveillance systems are ubiquitous and continuously producing large amounts of data, manual surveillance is required to identify human activities in the public realm. Meanwhile, smart surveillance systems that can identify normal and abnormal activities are urgently needed because they allow for the effective monitoring of images sent from cameras that are designed to capture abnormal activities; the implementation of these systems can alleviate the lack of surveillance personnel [42,43]. Furthermore, the inclusion of these systems can enhance the community's control over the number of people entering the mountain and the entry of unauthorized personnel.…”
Section: Using Contemporary Scientific Methods and Equipment To Enhan...mentioning
confidence: 99%
“…The experiments concluded that their method achieved higher accuracy as compared to randomly initialized filters. Similarly, Hussain et al [ 16 ] have proposed a lightweight 3D CNN model for anomaly activity recognition and camera prioritization in surveillance environments. The variants of 3D CNNs include two-stream 3D CNN [ 17 ], pseudo-3D CNN [ 18 ], and MiCT-Net [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the existing 3D-CNN models can only process 10 to 16 frames effectively. They cannot recognize lengthy activities due to exponential increase in time complexity caused mainly by the temporal dimension [ 16 ]. To overcome this issue, researchers experimented on hybrid models where the spatial features are extracted from pretrained CNN models and learned the temporal information using variants of Recurrent Neural Networks (RNNs).…”
Section: Introductionmentioning
confidence: 99%